The Runaway Production Complex? The Film Industry as a Driver of Urban Economic Revitalization in the United States. (September 2015) - Gautney, Heather; Rhomberg, Chris
Cities and states across the United States have turned to cultural industries to revitalize their economies, but we argue that the dynamics of agglomeration and labor market governance are crucial to the prospects for local economic growth from these sectors. This paper analyzes recent changes in the American film industry, traditionally a "high road" model of flexible production and employment. We examine the rapid rise of state tax incentives and spatial dispersal of production within the United States, the destabilization of traditional industrial complexes in California and New York, and the development of new centers in states like Louisiana and New Mexico. Our findings suggest that the spatial fragmentation of the industry is undermining established forms of regulation, introducing a new volatility in the labor market, and challenging the ability of localities to benefit from growth in the industry.